Tidal zone effects on the diet composition of leaf-eating crabs in natural mangrove communities: a stable isotope analysis - Lu, Xiaoyan; Gu, Xuan; Zhang, Lin; Zhang, Jinhan; Wang, Wenqing; Wang, Mao (Frontiers in Marine Science, 2024)
In natural mangrove communities, mangrove species are often distributed zonally. Leaf-eating crabs are one of the most abundant and iconic arboreal brachyurans in mangrove forests, but variation in the composition of crab diets in different mangrove tidal zones is unknown. To determine the contributions of mangrove leaves and other organic carbon (C) sources to leaf-eating crab diets, dual stable C and nitrogen (N) isotope signatures (δ13C and δ15N) were used in a Bayesian stable isotope mixing model. We conducted experiments at various tidal levels in the Dongzhaigang Bay National Natural Reserve in China. We analyzed δ13C and δ15N of leaf-eating crabs, mangrove leaves, sediment organic matter (SOM), and animal tissues (prey). Food composition of the dominant crab Parasesarma continentale differed in the four tidal zones. From the margin to the high tide zone, the main food source shifted from predominantly mangrove leaves and SOM to primarily SOM and animal tissues. We observed a significant negative relationship between the C/N ratios of mangrove leaves and the proportion of leaves consumed by leaf-eating crabs. Additionally, as the tidal level increased, the C/N ratio of mangrove leaves also increased, whereas the proportion of leaves consumed by crabs decreased. Thus, the diet of leaf-eating crabs differed significantly between tidal zones, indicating that the diet of consumers needs to be studied by differentiating tidal zones.